Determination of the chemical composition of acorn (Quercus branti), Pistacia atlantica and Pistacia khinjuk seeds as non-conventional feedstuffs - Saffarzadeh, Ali; Vincze, László; Csapó, János (Acta Agraria Kaposváriensis, 1999)
An experiment was conducted to determine the chemical composition of acorns, Pistacia atlantica and Pistacia khinjuk by sampling seeds from 3 different climates in the Zagrossian region of Iran from an area of about 500,000 hectares offorests. The seed samples were analysed for dty matter, protein, fat, fibre, ash, starch, minerals, amino acids and fatty acids. It was established that acorn have a very low crude protein content and a relatively high starch and crude fat content. Their amino acid composition is very poor; their protein contains, in particular, very few sulphur-containing amino acids (cystine and methionine). Their fat contains considerable quantities of essential linoleic acid. The crude protein content of wild pistachios seeds is very similar to that of corn, and a little lower than that of the other grains. Pistachio protein has a relatively high amount of threonine, serine, valine and lysine, which is very important if it is to be used as poultry feed. The crude fat content of Pistacia khinjuk is 39.10%, that of Pistacia atlantica 26.80%, with a very high content of essential linoleic acid, which is very useful in poultry nutrition.
Keywords: Acorn; Pistacia atlantica; Pistacia khinjuk; chemical composition; protein